Effect of aging state on microstructure and properties of heat affected zone in Al–Mg–Si–Cu alloy welded joints - Yang Tao; Shuncun Luo; Jiajie Zhang; Xiaonan Wang; Xiaming Chen; Zengrong Hu; Hiromi Nagaumi (Journal of Materials Research and Technology)
The softening of the heat affected zone (HAZ) remains a significant challenge in fusion welding of novel Al–Mg–Si–Cu alloy, and the underlying mechanisms vary across different aging states. However, limited research has been conducted on this topic. Therefore, this study investigates the influence of various aging states on the microstructure and mechanical properties within the HAZ of welded joints by selecting extrusions treated with T4, T5, and T6 heat treatments. The results indicate that the increase in hardness of HAZ I is attributed to solid solution strengthening. In the HAZ I, the precipitated phases are mostly dissolved into the matrix under the influence of a peak temperature of 464.6 °C, and no residual precipitated phase is detected in T4 and T5 alloy joints, while some undissolved Q phase is observed in T6 alloy joint. The decrease in hardness of HAZ Ⅱ is attributed to the limited precipitation of coarse β'' and Q' phases for the T4 alloy welded joints, which weakens the solid solution strengthening. However, the softening mechanisms in the HAZ Ⅱ of the T5 and T6 alloy joints are ascribed to the dissolution of β'' and subsequent precipitation of Q' and Q phases. HAZ Ⅲ, close to the base metal, exhibits a lesser degree of influence and thus experiences a gradual recovery in hardness. This study can provide theoretical guidance for the exploration of high-strength, heat-resistant aluminum alloys.